Attitudes toward COVID-19 Vaccine Uptake: A Qualitative Study of Mostly Immigrant Racial/Ethnic Minority Older Adults - Carla Valero-Martínez; Christopher Martínez-Rivera; Jenny Zhen-Duan; Marie Fukuda; Margarita Alegría (Geriatrics, 2023)
(1) Background: Few qualitative studies address diverse older adults’ perceptions of COVID-19 vaccination in the United States, including non-English speakers and immigrant populations. This study aims to understand the attitudes of diverse, primarily immigrant older adults in the U.S. toward the COVID-19 vaccine and its influences on their vaccination decision-making. (2) Methods: The research team conducted semi-structured interviews (N = 100) in 2021 focused on understanding ethnically/racially diverse older adults’ perceptions of the COVID-19 vaccine. Interviews were recorded, coded, and analyzed using a thematic analysis approach. (3) Results: Thematic analyses identified three themes. (1) Older adults showed mixed attitudes toward the COVID-19 vaccine associated with information consumed and trust in healthcare systems; (2) health concerns and underlying medical conditions were the most influential factors of vaccine uptake; and (3) systemic barriers and trusted figures impacted vaccination decision-making of older adults. (4) Conclusions: Accessible information in diverse languages tailored to the community’s fears is needed to combat vaccine mistrust. Vaccine rollout programs need to tackle the fear of vaccine side effects. Attitudes of religious leaders, family members, and physicians considerably influenced vaccine uptake, suggesting their role as trusted members for vaccine messaging for older, primarily immigrant adults. Systemic barriers, namely lack of transportation and inaccessible vaccination sites, contributed to vaccine deterrence.